The association of HIV and easy access to narcotics in Pakistan; calling drug policy makers - Tauqeer Hussain Mallhi; Yusra Habib Khan; Amjad Khan; Nasser Hadal Alotaibi; Abdulaziz Ibrahim Alzarea; Furqan Khurshid Hashmi (Taylor & Francis Group, 2019)
HIV in Pakistan is concentrated to people who inject drugs (PWID) and easy accessibility of narcotics to this population cannot be disregarded as a risk factor of growing encumbrance of AIDS in the country. All the narcotics and other medications having high potential of abuse are stratified into Schedule G of Punjab Drug Rules 2017. According to these rules, drugs in Schedule G shall be sold in pharmacy under the direct supervision of qualified pharmacist. However, Schedule G is not implemented in Punjab due to continuous resistance from pharmaceutical stakeholders including medical store owners (who are barred to sell drugs from schedule G). Since 1.6 million PWID reported misuse of prescription opioids for non-medical use, delayed implementation of schedule G is attributing to the unabated sale of narcotics without prescription and for non-medical purposes, which is further contributing to the staggering number of PWID in the country. Implementing schedule G will not only curb the existing situation of HIV but will also mitigate the contribution of PWID towards the future events.